A search for pair production of new light bosons decaying into muons - (:unkn) unknown (ELSEVIER, 2016)
A search for the pair production of new light bosons, each decaying into a pair of muons, is performed with the CMS experiment at the LHC, using a dataset corresponding to an integrated luminosity of 20.7 fb(-1) collected in proton-proton collisions at center-of-mass energy of root s = 8 TeV. No excess is observed in the data relative to standard model background expectation and a model independent upper limit on the product of the cross section, branching fraction, and acceptance is derived. The results are compared with two benchmark models, the first one in the context of the next-to-minimal super-symmetric standard model, and the second one in scenarios containing a hidden sector, including those predicting a nonnegligible light boson lifetime. (C) 2015 CERN for the benefit of the CMS Collaboration. Published by Elsevier B.V.
Keywords: LHC; CMS; Muon; NMSSM; Hidden sectors; Dark matter; NEUTRAL HIGGS BOSONS; BROKEN SYMMETRIES; OPAL DETECTOR; GAUGE; SUPERSYMMETRY; E(+)E(-); MASS